Incidence of inhibitor development in PUPs with severe Haemophilia A in the CEE region between 2005 and 2015. Issue 198 (February 2021) - Blatný, Jan; Kardos, Mária; Miljic, Predrag; Bilić, Ernest; Benedik-Dolničar, Majda; Faganel-Kotnik, Barbara; Konstantinov, Dobrin; Kovalova, Zhanna; Ovesná, Petra
Abstract: Introduction: This study analyses real-world data on 144 previously untreated patients (PUPs) with severe Haemophilia A, from seven countries in Central and Eastern Europe (CEE: Bulgaria, Croatia, Czech Republic, Hungary, Latvia, Serbia, and Slovenia), over a period of 11 years. It analyses the risk factors associated with development of inhibitors to factor VIII concentrates. Methods: Cox proportional hazard models were used to estimate the hazard risk of factors possibly influencing the development of inhibitors. Patients were followed for up to 100 exposure days (EDs). Results: Cumulative inhibitor incidence at the time of 100 EDs was 18.7%, slightly lower than the 25–35% incidence reported in most studies. Of PUPs who developed inhibitors, a majority (56%) developed them within the first 20 EDs and 88% by the 50th ED. FVIII class (recombinant or plasma-derived) did not influence the inhibitors' incidence rate ( p  = 0.64). We found a significant protective effect of prophylaxis compared to on-demand treatment ( p  = 0.003). PUPs who had an intensive peak treatment during the first 50 EDs were at significantly higher risk for inhibitor development (HR (95% CI) 5.3 (2.3–12.5), p  < 0.001). Conclusion: Inhibitors are and will continue to be the most significant complication of haemophilia treatment with factor concentrates. This is particularly true for haemophilia A. In our cohort, we were able to show that the treatment regimen used during first 50EDs influenced significantly the inhibitor risk, but the class of the factor concentrate did not play an important role. Real world data will remain one of the important resources for improving our knowledge of haemophilia. Highlights: 144 PUPs with Haemophilia A from seven countries in Central and Eastern Europe Prophylaxis significantly protects against inhibitor development. FVIII class does not influence incidence of inhibitor development. Intensive peak treatment in first 50 EDs increases risk of inhibitor development.